The house of Ottoman Sultan - The architectural space organization of Ottoman palaces - Sagdic, Z (WIDE DREAMS PROJECTOS MULTIMEDIA LDA, 2002)
While considering world architecture under of political, socio-economical and cultural effects, without any doubt, the concept of Ottoman architecture has to be studied. Ottoman palaces are very important examples of world architecture with their architectural space organisation. They are not only governmental centre, but also houses of sultans. Thus, Ottoman palaces have to be studied, within the parallelism of governmental changes of Ottoman Empire, technological developments and changes of urbanistical living conditions of Ottoman society. The importance of new Ottoman palaces, which were designed as results of changes on space organisation of classical Ottoman palaces, has not been so touched until today. These palaces are still standing as the documents of political and cultural changes in modernisation movements of Ottoman civilisation. It must not be forgettable that, as a wind of being western, modernisation movements firstly influenced the life of Ottoman dynasty and therefore influenced Ottoman palaces as the house and the governmental centre of Ottoman dynasty. While studding on existing documents and writings of both Ottoman historians and the western travellers of that era, and while comparing examples of Ottoman palaces within each other, the importance of the concept of being modern and/or the concept of modernisation on the Ottoman mentality world have to be clearly understood.
Keywords: saray-i humayun; space organization; Ottoman Empire; urbanisim; palace; kiosk; Architecture; Construction & Building Technology; Engineering; Environmental Sciences & Ecology; Urban Studies